Evaluation of substrates and organic fertilizers in the acclimatization of plantlets of Heliconia psittacorum - Santos, Maurício Reginaldo Alves dos; Timbó, Ana Luiza de Oliveira; Carvalho, Ana Cristina Portugal Pinto de; Morais, João Paulo Saraiva (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the efficiency of three organic substrates, carbonised rice hull, dry and green coir dust, and two fertilizers, Vitasolo® and earthworm humus, in the acclimatization of plantlets of Heliconia psittacorum L., obtained from micropropagation. After 75 days, the height of the plants, diameter of pseudo-stem, number of leaves and area of the third leaf were evaluated. The rice hull was more efficient than the coir dust (dry or green); the green coir dust was more efficient than dry coir dust; and the humus was more efficient than Vitasolo®.